The Chelsea Porcelain Case, British Galleries, The Metropolitan Museum of Art - Iris Moon (Yale University, 2021)
When visitors to the museum encounter carefully curated displays behind glass, the arrangements they see are the outcome of intense discussions, conversations, and dialogues, many of which span years. In an effort to open up the curatorial process to a broader audience, British Art Studies invited a group of curators and academics to participate in a round table discussion focusing on a case in The Metropolitan Museum of Art’s British Galleries containing Chelsea porcelain, which each discussant had seen in person. The display, which served as a case study for pondering the challenges of curating and interpreting race and empire in a decorative arts gallery context, is unusual in that it combines useful porcelain wares such as plates alongside sculptural forms made as art works. Such an arrangement is not typical of decorative arts displays, which tend to separate wares for the table from ornamental sculpture. Even prior to the opening of the British Galleries in the spring of 2020, the case proved particularly challenging to configure, given its location in the central axis of the space devoted to the eighteenth century. An earlier iteration featuring Joseph Willems’s (1715–1766) terracotta sculpture of a Black man holding a mixing bowl in the center of the case prompted questions for the curatorial team of how race figured in the broader narratives of the British Galleries. Save for Josiah Wedgwood’s antislavery medallion, the sculpture marks the only Black presence in the entire suite of galleries. Although the decision was ultimately made to pivot the figure so that it faced north instead of being on axis, the impact of such a slight change in the arrangement prompted a larger discussion about what role the placement of works and museum displays play in propagating or challenging narratives from the past. The coordination or disjuncture between object and label, case height, as well as the visual and spatial relationships established between works within a display became crucial factors in recontextualizing and generating new perceptions in a three-dimensional format. Following the round table discussion, each participant contributed a response to the case, which provided a rich “object” for rethinking the British decorative arts.